TANTANGAN ETIKA PROFESI GURU PPKN DI ERA DIGITAL: ANALISIS PENGGUNAAN MEDIA SOSIAL, PERLINDUNGAN PRIVASI SISWA, DAN INTERAKSI DARING - Daria Darmawati Gea; Harni Sartika Marulafau; Febriana Sri Yulianti Putri Gulo (Jurnal Binagogik, 2026)
Digital transformation in education has brought both positive and negative impacts on the teaching profession. Teachers as professional educators are required not only to master pedagogical, social, professional, and personal competencies, but also to apply digital ethics. This study aims to analyze the challenges of professional ethics for Civic Education (PPKn) teachers in the digital era, particularly regarding social media use, student data privacy protection, and online interaction with parents. The study employed a qualitative descriptive method with a case study approach. Data were obtained through observation, interviews, and documentation during Teaching Assistance activities. The results show that uncontrolled social media use by teachers can diminish professional authority. Additionally, a low level of understanding regarding student personal data protection was found among teachers. In online communication, teachers also face challenges from parents demanding immediate responses that often exceed the professional boundaries of teachers. This study recommends the importance of drafting a digital code of ethics for teachers, digital literacy training, and increased legal awareness regarding personal data protection.